Influences of dietary aspirin supplementation on growth performance, carcass characteristics and gastrointestinal organs of broilers - Tavakoli, Masoomeh; Bouyeh, Mehrdad; Seidavi, Alireza (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was performed to investigate the effect of dietary aspirin (A) on some performance traits in broilers using a completely randomized design, 120 one-day-old male broiler chicks Ross 308, three levels of aspirin (0, 50, and 100 mg/kg), in 4 replicates, each including 10 chicks, during 42 days. The effects of different levels of aspirin, added to a basal diet, on performance, carcass characteristics, and digestive organs of chicks were investigated. Data analysis was performed by SAS statistical software and the comparison of the means with Duncan’s test. The results showed that the chickens fed by a diet containing 100 mg/kg of aspirin had the highest feed intake and weight gain and the best feed conversion ratio compared to the other treatments. Also, the lowest production cost and the best European factor were related to treatment A100 (P<0.05). In addition, the use of the same level of aspirin resulted in a significant increase in some carcass properties and a decrease in ventricular fat compared to the control (P<0.05). So, based on the results of the present study, the use of 100 mg/kg aspirin in the diet of broilers is recommendable to improve some performance parameters.